TELAAH PEMBUKTIAN TERBALIK TINDAK PIDANA PENCUCIAN UANG DALAM PROSES PERADILAN - Hudi Yusuf; Istiqomah; Fatrulah Puspita Sari (Program Magister Ilmu Hukum Universitas Pancasila, 2022)
Money laundering or money laundering is simply defined as a process of making the proceeds of crime or referred to as dirty money, for example the proceeds from drugs, corruption, tax evasion, gambling, smuggling and others, which are sought or transformed into a form that looks legitimate for safe use. Indonesia only criminalized money laundering in April 2002, with the promulgation of Law Number 15 of 2002 concerning the Crime of Money laundering, which was later revised by Law Number 25 of 2003. After that, in 2010, the anti-money laundering provisions were revised again with Law Number 8 of 2010. Law on money laundering crimes. the crime of money laundering has different characteristics from other types of crime in general, especially that this crime is not a single crime but a double crime. The law on the crime of money laundering does not provide a definite definition regarding the crime of money laundering whether it is a further offense or an independent one, this has arisen in academics and activation law regarding the crime of money laundering whether it is an independent or a further offense. The formulation of the articles that form the basis of these violations are Article 3, Article 4, Article 5 and Article 69 of the crime of money laundering. The type of research conducted is normative research, the approach used is the statutory approach and the conceptual approach, the legal materials used come from the literature, journals and invitation regulations, data collection techniques are using document studies, analysis of legal materials is by using protection . The conclusion that the crime of money laundering is a follow-up criminal act, meaning that the money laundered by the perpetrator is none other than a predicate crime, so that a money laundering crime can occur without being preceded by a predicate crime